Screening of metabolic markers present in Oxytropis by UHPLC-Q-TOF/MS and preliminary pharmacophylogenetic investigation - Jia, Xin; Liu, Yang; Wang, Suwei; Ma, Jiannan; Yu, Juan; Yue, Xin; Zhang, Ying; Wang, Xiaoqin (Frontiers in Plant Science, 2022)
Plants belonging to the Oxytropis genus, family Leguminosae, are found throughout the world, with about 80 species mainly distributed in northwest and northeast China. The plants have medicinal properties and many plants have been used as folk medicine for the treatment of colds, inflammation of carbuncle swelling, pain, and different types of bleeding. In recent years, due to the reduced availability of wild resources and increased clinical demand, additional Oxytropis species have been used in Mongolian medicine. This study explored the medicinal potential of four Oxytropis species, investigating their phylogeny, chemical components, and pharmacological activities. Oxytropis myriophylla (Pall) DC., Oxytropis hirta Bunge, and Oxytropis bicolor Bge. were found to be closely related at the taxonomic level. While previous investigations on the bioactive constituents of Oxytropis have been limited and have concentrated largely on flavonoids and saponins, the present study established a novel UHPLC-Q-TOF/MS based on metabolite profiling to comprehensively analyze the chemical composition of the four Oxytropis species and to identify marker compounds. A total of 75 compounds were identified from the four species, with 23 identified as characteristic marker components. Twenty-six marker compounds were identified in O. myriophylla from different geographical regions. Analysis of pharmacological activity showed that extracts of O. myriophylla and O. hirta had stronger anti-inflammatory activity than the extracts from the other species. The relationships between the chemical components, traditional curative uses, and pharmacological activities were analyzed to provide a preliminary documentation of the pharmacophylogenetic characteristics of the Oxytropis family as a whole. Several marker compounds, including licoricesaponin G2, licoricesaponin J2, and glycyrrhizic acid found in O. hirta were found to have effective anti-inflammatory activity, consistent with the traditional application of reducing swelling and healing wounds. This preliminary investigation into the pharmacophylogeny of the genus Oxytropis will contribute to the conservation and exploitation of the medicinal resources of this genus.